Behavioral and contextual determinants of different stages of saving behavior - Barrafrem, Kinga; Tinghög, Gustav; Västfjäll, Daniel (Frontiers in Behavioral Economics, 2024)
Introduction Saving is a journey, beginning with the critical decision to initiate the process, take that pivotal first deposit step, and persistently commit to ongoing savings. However, a lot of saving plans fail already before any deposit is made, and even if the first deposit is made, long-run success of savings is far from guaranteed. In this study, we investigate both individual and saving-goal-specific determinants of successful savings. Method We use real-life savings data (N = 2,619 saving goals of 808 individuals) from a FinTech company in Sweden that helps individuals save for their goals. In addition, we collect a wide range of individual characteristics related to financial behavior: individuals' objective and subjective financial knowledge, self-control, and information avoidance. Results and discussion Our analysis uncovered distinctive patterns at different stages of the saving process. While objective financial knowledge didn't correlate with how much one saves, it was significantly related to the likelihood of making the first deposit. Furthermore, individuals with high self-control exhibited greater savings, though self-control was not related to the initiation of saving. Interestingly, subjective financial literacy and information avoidance showed no significant association with overall savings behavior. Additionally, our study indicated that the attainability of goals plays a crucial role in depositing funds, with more achievable goals having higher deposit likelihoods. Conversely, ambitious goals, despite their challenging nature, tended to attract more substantial savings. Our findings, grounded in real-life data, provide valuable insights into the intricate mechanisms influencing successful saving behaviors, shedding light on the complexities of financial decision-making and goal pursuit.